Modernization of Irrigation System Operations - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Proceedings of the fifth international Information Techniques for Irrigation Systems (IT IS) network meeting, India, 28 30 October 1998.FAO, IWMI & CEMAGREF, 1999.262 pp.ISBN 974 85777 9 1Available at postage rateFAO regional office for Asia and...